Daily strategies for the production of narrative texts - Cámara-Acero, Percy (2020)
The production of narrative texts; it must be a constant practice in the students; However, they have difficulties for not knowing strategies that allow them to write easily. For this reason, the research work aimed to demonstrate the influence of the application of everyday strategies for the production of narrative texts. The method used was the deductive inductive and the synthetic analytical; which corresponded to the level of experimental research, applied type and quasi-experimental design. The population consisted of 270 students; The sample was non-probabilistic, non-standard or circumstantial sampling with 30 students from the 5th “A” (experimental group) and 5th “B” (control group), with the application of the pretest and posttest. In the first group, daily strategies were applied; and in the second, the conventional approach. Through the result of the post test, the influence of the strategy could be determined; since 80% of the students in the experimental group are in expected achievement and 20% in outstanding achievement respectively. In conclusion, everyday strategies significantly influence the production of narrative texts, generating meaningful learning for students.